Indonesian Rheumatology Association (IRA) Recommendations for Diagnosis and Management of Axial Spondyloarthritis 2021 - Ayu Paramaiswari; R.M. Suryo Anggoro Kusumo Wibowo; Yulyani Werdiningsih; Arief Nurudhin; Surya Darma; Lita Diah Rahmawati; Sumartini Dewi; Rudy Hidayat; Sumariyono (Indonesian Journal of Rheumatology, 2021)
Objective. Recommendations for spondyloarthritis are made to provide guidelines in diagnosis establishment, therapy, and monitoring of axial spondyloarthritis cases.Method. Literature searches were conducted online. The drafting team determines the levels of evidence (LOE) and grades of recommendation (GOR). After conducting a discussion, each recommendation that has been agreed upon by the drafting team is then classified based on the levels of evidence and grades of recommendation. The final step in the preparation of these recommendations is to determine the level of agreement (LOA) on each recommendation carried out by a team of panelists who have been appointed by IRA.Results. Twenty recommendations regarding axial spondyloarthritis were established. Strong recommendations or GOR A include: Ax-SpA diagnosis can be made according to the 2010 ASAS criteria, or the 1984 modified New York criteria specifically for the US; conventional radiographic examinations and MRI of the sacroiliac joints and vertebrae may be used as evaluators of disease activity and predictors of therapeutic response, as well as patients who do not respond to NSAIDs (within 4 weeks) can be administered a combination of NSAIDs and anti-TNF, and if it is not possible, a combination of NSAIDs and anti-IL-17A (Secukinumab, Ixekizumab).Conclusion. These recommendations provide a direction for clinicians to diagnose and manage spondyloarthritis.